2019
DOI: 10.1159/000500373
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Status and Kidney Health of Factory Workers Exposed to Heat Stress: A Pilot Feasibility Study

Abstract: Dehydration associated with heat stress increases the risk of workplace injury or illness, decreases productivity, and may contribute to the chronic kidney disease epidemic identified in outdoor workers from hot climates. There is limited research on the effects of chronic occupational heat stress among indoor workers. We aimed to test the feasibility of measuring markers of hydration and kidney function in foundry factory workers in Southern Brazil, exposed and not exposed to heat stress. Factory workers expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
2
17
0
2
Order By: Relevance
“…Decreased kidney function can be experienced by workers suffering from heat stress or conditions that can cause heat stress such as poor rehydration. 6,10,11 Heat stress, exposure to heat for more than 6 h, heavy workload, inadequate rehydration, and lack of proper rest periods can also cause acute kidney disease. [12][13][14][15][16][17][18][19][20][21] If this condition is experienced by workers continuously, heat stress can also increase the risk of chronic kidney disease.…”
Section: Resultsmentioning
confidence: 99%
“…Decreased kidney function can be experienced by workers suffering from heat stress or conditions that can cause heat stress such as poor rehydration. 6,10,11 Heat stress, exposure to heat for more than 6 h, heavy workload, inadequate rehydration, and lack of proper rest periods can also cause acute kidney disease. [12][13][14][15][16][17][18][19][20][21] If this condition is experienced by workers continuously, heat stress can also increase the risk of chronic kidney disease.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, the impact of hypohydration on aspects of worker health beyond the workplace has begun to be elucidated. For instance, repeated exposure to a hypohydrated state caused by severe physical work in the heat has been proposed to bring about chronic kidney disease, which is speculated to be due to the workers experiencing repeated bouts of subclinical kidney injury (Glaser et al., 2016 ; Hansson et al., 2020 ; Johnson et al., 2019 ; Mix et al., 2018 ; Nerbass et al., 2017 , 2019 ; X. Yang et al., 2020 ). Cases of chronic kidney disease have been reported in workers performing manual work in hot environments in hottest regions in the world (Aguilar & Madero, 2019 ; Butler‐Dawson et al., 2019 ; Glaser et al., 2016 ; X. Yang et al., 2020 ).…”
Section: Narrative Reviewmentioning
confidence: 99%
“…Construction workers also risk developing kidney damage, as indicated in previous studies [20][21][22]. On the contrary, in some studies, no statistically significant difference has been observed between workers with and without HS in kidney function biomarkers [23][24][25]. Controversy can be observed between studies investigating the effect of HS on kidney function.…”
Section: Introductionmentioning
confidence: 96%